The Commodification of Religion in the MaqÄá¹£id Al-Shariah Perspective - Maftukhatusolikhah, Maftukhatusolikhah; Rusydi, Muhammad (IAIN Samarinda, 2018)
This article discusses the problem of the commodification of religion in Islam, namely looking at the perspective of Islamic law on a process that directs the symbols and religious expressions of Muslims in the framework of market-based power as a commodity or business object. The theory used is the Maqashid ash-Shariah theory, to find out whether or not the objectives of sharia law are maintained in the religious practices which intersect with the economic dimension. This becomes relevant because for a Muslim the conformity with the objectives of sharia is the materialization of maslahah which is the wisdom of establishing a law in Islam. It employs a normative approach in the perspective of Maqashid jurisprudence. The results of this study indicate that in the Islamic context, there are several things that reveal the symptoms of religious commodification which are packaged in various forms of industry. Some types of industry still exist which are built with economic rationality to seek mere worldly benefits and ignore the principles of benefit. For this type of business practice, the government with its various instruments or institutions must continue to carry out sharia-compliant supervision. Meanwhile for the sharia-based business practices or industries, there is no legal issue in complying with sharia objectives there.Keywords:Â Commodification of religion, Maqasid al-Sharia, Islamic law, religion with economic dimensions.